Analysis of blue carbon storage in Scottish rhodolith bed - Kelly James; N A Kamenos; H L Burdett (PANGAEA, 2024)
Previous research has identified that Scottish rhodolith beds store organic carbon, however, such research has been limited to one site (Mao et al., 2020; https://doi.org/10.1111/gcb.15021). In this study we took sediment cores from 4 additional rhodolith beds in Scotland during September 2019. The sites sampled were Loch Torridon (57.541167 , -5.532167), Sound of Barra (57.052356 , -7.415361), Sound of Eriskay (57.094361 , -7.297278), Tingwall (Orkney; 59.087722, -3.038861). Cores were extracted via scuba using a drop hammer. One core was extracted per site, with the cores split into 1cm sections. The cores were sieved into fraction sizes (<63μm, 63-250μm, 250-500μm and >500μm). Fractions <63μm 63-250-μm and 250-500μm were analysed via stable isotope analysis to determine the OC wt%, δ13C and δ15N. CaCO3 wt% was determined by loss after acidification with HCl. The carbon reactivity index (CRI; Smeaton and Austin 2022; doi:10.1029/2021GL097481), was determined via Thermogravimetric Analysis. The data was collected to determine the current sedimentary OC stock and to determine the amount of blue carbon stored in Scottish rhodolith beds. δ13C and δ15N was used to determine the source of OC, with end members used to characterise the δ13C and δ15N of organic material sources near the rhodolith beds.